Atopic Eczema Dan Komorbiditas Kondisi Psikologis: Bagaimana Hubungan Dan Tatalaksananya - Nurkhalifah, Ninda; Sasmitha Ajiningrum, Ridha; Basyir, Ilma; Atsani, Genta; Ilawanda, Zanetha (Jurnal Syntax Fusion, 2022)
Atopic eczema or atopic dermatitis (AD) is a chronic recurrent inflammatory skin disease. Atopic dermatitis is almost 20% in children and 10% in adults. The etiology of atopic dermatitis is genetic and environmental factors that cause abnormalities in the epidermis and immune system. To determine the psychological comorbidities of atopic dermatitis patients and their management. The writing of this article includes various sources originating from scientific journals on online portals of journal publications such as Medscape, Google Scholar, PubMed, and NCBI, with the keyword “Eczema Atopic” Individuals with AD are at risk for psychological disorders. Psychiatric comorbidities that can occur in AD patients are depression, anxiety, stress, behavioral disorders, and psychosis. Atopic dermatitis has a major impact on the mental health and quality of life of individuals with AD as a result of intense itching, unpredictable disease, and feelings of disability caused by skin lesions. Individuals with atopic eczema are more likely to experience depression and anxiety because of the effects of itching and discomfort, disability, and perceived social stigmatization. Lack of sleep due to itching at night can increase the risk of mental disorders. This causes individuals with AD to have a lower quality of life and higher stress levels than healthy individuals.